Implementation of Lumi-lumi (Harpodon nehereus) Fish Fillet Processing Methods as Salted Fish to Short Drying Time - Rosi Rahayu; Muhammad Arif; Rahmawati Rahmawati; Akbardiansyah Akbardiansyah; Sri Ayu Insani; Hamidi Hamidi; Afdhal Fuadi; Ikhsanul Khairi; Muhammad Agam Thahir; Rudi Hermi (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2023)
The downstream fishing industry in the form of fish processing has great potential to improve community welfare. In addition to providing added value to fishery products, fish processing is one solution if there is an overproduction of fishery catches. Salted fish processing producers at MSMEs Jaya Salted Fish in Langkak Village, Kuala Pesisir District, Nagan Raya Regency are currently continuing to improve production efficiency for production optimization. There are technical limitations in terms of production efficiency by partners so that counseling and training on improving production efficiency are needed. The methods used in this service are counseling and training. This activity was carried out at the MSME Jaya Ikan Asin unit in Langkak Village, District. Kuala Pesisir Nagan Raya Regency on October 1-2, 2022. This activity began with the manufacture of fishery products in the form of Bombay Duck salted fish. In this activity, there are several stages of activities, namely surveys, salted fish processing processes, and salted fish drying. This activity is carried out well so that it can increase the number of types of Bombay Duck salted fish production in MSMEs jaya salted fish